The Current State Baan Chokchai Child Development Center Management Under the Truat Tambon Administrative Organization Srinarong District, Surin Province - Boonsri, Pattamaporn (Academic MCU Buriram Journal, 2023)
The purposes of this research were: 1) to study the administration of Ban Chokchai Child Development Center under the Truat Sub-District Administrative Organization, Srinarong District, Surin province; 2) To study the proposal of Ban Chokchai Child Development Center under the Truat Sub-District Administrative Organization, Srinarong District, Surin Province. The samples used in the research were 1 president of the Tambon Administrative Organization, 1 academician, 1 school head of Ban Chokchai Child Development Center, 6 child care teachers, 16 parents, and the Chokchai Child Development Center Committee under the Tambon Administrative Organization, Srinarong District Surin Province, 15 people, total population 40 people. The tools used in the research were questionnaires. The statistics used in the data analysis were basic statistics, percentage, mean and standard deviation. The research results found that: The administration of Ban Chokchai Child Development Center as a whole, general administration, personnel, academic and curriculum activities, participation and support from all sectors, and promotion of early childhood development networks at a high level. As for building, place, environment and safety, they were at moderate levels. Guidelines for the development of the administration of Ban Chokchai Child Development Center are as follows: 1) General management should develop a playground to have equipment that enhances child development adequately, improve information communication processes, have a joint operation plan with stakeholders, and outsiders to participate in activities, should provide a performance evaluation and continuous supervision. 2) In terms of personnel, the selection of teachers should be improved to have a suitable number of children by developing the potential of teachers' performance. 3) In terms of buildings, environment and safety, there should be improvements to fences around the perimeter, repairing roofs, damaged ceilings, and improving walkways to have a roof for children to go to the cafeteria. 4) Academic and curriculum activities should provide activities to promote learning and development of physical, emotional, mental, social and intellectual aspects in accordance with the curriculum and develop desirable characteristics of early childhood children, organize activities to promote child rearing according to lifestyles, community contexts by coordinating cooperation between families and communities in child development. 5) In terms of participation and support from all sectors, learning activities should be organized for child development by requesting cooperation from communities, parents, and relevant agencies. 6) The promotion of early childhood development networks should create early childhood development networks with other areas to share knowledge and experiences for use in the management of early childhood development centers. Teachers should encourage children to be interested in activities, learning together with parents.